The plant-based solution eaudiobook America's healthy heart doc's plan to power your health. - Kahn, Joel K, MD (HighBridge Audio, 2018)
Are you ready to feel better, look better, and heal the planet at the same time? Then it's time to revolutionize your health from the inside out. With The Plant-Based Solution, leading cardiologist Dr. Joel Kahn shows how everyone can cultivate optimal well-being with a whole-foods, plant-based diet. Known as America's Healthy Heart Doc, Dr. Kahn has already helped thousands of people prevent and reverse heart disease. But what about other chronic conditions, such as adult diabetes, obesity, gut health, osteoporosis, autoimmune disease, and even low sex drive? It turns out that all these conditions and more can be improved with a plant-based diet-and Dr. Kahn has the evidence to prove it. Drawing from decades of experience, Dr. Kahn brings together a wealth of scientific research and in-depth case studies to clearly demonstrate how you can take charge of your own health.